2009
DOI: 10.1007/s11010-009-0260-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of noradrenaline-induced stimulation of Na–K ATPase activity in the rat brain: implications on REM sleep deprivation-induced increase in brain excitability

Abstract: Rapid eye movement (REM) sleep is a unique phenomenon expressed in all higher forms of animals. Its quantity varies in different species and with ageing; it is also affected in several psycho-somatic disorders. Several lines of studies showed that after REM sleep loss, the levels of noradrenaline (NA) increase in the brain. The NA in the brain modulates neuronal Na-K ATPase activity, which helps maintaining the brain excitability status. The detailed mechanism of increase in NA level after REM sleep loss and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…In addition, it was shown that the increased expression of α1-NaKA was developmental and preceded the increased expression of NaV1.6 and ankyrin-G (Kaphzan et al, 2011). It has been shown that increased expression and activity of α1-NaKA lowers the resting membrane potential and induces a less excitable state (Brodie et al, 1987; Gadsby, 1984; Mallick et al, 2010; Silva et al, 2006). Moreover, it was shown that disrupting presynaptic input, which also decreases neuronal excitability results in AIS changes similar to what was observed in AS model mice (Kuba et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was shown that the increased expression of α1-NaKA was developmental and preceded the increased expression of NaV1.6 and ankyrin-G (Kaphzan et al, 2011). It has been shown that increased expression and activity of α1-NaKA lowers the resting membrane potential and induces a less excitable state (Brodie et al, 1987; Gadsby, 1984; Mallick et al, 2010; Silva et al, 2006). Moreover, it was shown that disrupting presynaptic input, which also decreases neuronal excitability results in AIS changes similar to what was observed in AS model mice (Kuba et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…NA is one of the key neurotransmitters involved in REMS regulation [14]; its level in the brain reduces during REMS [15] and increases during REMSD [3,16]. The NA-ergic neurons are predominantly concentrated in the LC of rats [17] and these neurons are primarily responsible for supplying most of the NA throughout the brain, including the dorsal raphe (DR), the main site for serotonergic neurons in the brain [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The DR neurons continue firing during REMS without atonia [21]. Further, since our previous studies have shown that REMSD-induced cytomorphometric changes in neurons were induced by NA [12] and that NA level increases in the brain after REMSD [16,22,23], we hypothesized that DR neurons also are likely to get affected by REMSD induced elevated levels of NA. Alzheimer's disease associated reduction in both REMS as well as serotonin level [24,25] supports our hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep can be categorized as non-rapid eye movement (NREM) sleep and rapid eye movement (REM) sleep [55]. These states of sleep are identified and classified based on variouselectrophysiological signals electroencephalogram (EEG) recorded from the brain and neck as well as the eye muscles [39]. NREM sleep is known as slow wave sleep (SWS) due to its synchronous slow-oscillation of membrane potentials in neurons of neocortex area [49].…”
Section: Categories Of Sleepmentioning
confidence: 99%
“…NREM sleep is known as slow wave sleep (SWS) due to its synchronous slow-oscillation of membrane potentials in neurons of neocortex area [49]. REM sleep, being an important component of sleep, is also known as active sleep, desynchronized sleep, or paradoxical sleep and is characterised by a desynchronised pattern, high frequency low amplitude waves in electroencephalogram, rapid eye movements and atonia in antigravity muscles [39].…”
Section: Categories Of Sleepmentioning
confidence: 99%